Comparing Two Different Initial Conditions AAMQS and Quartic Action in Illustrating the Effect of Valence Color Charges in High-Energy pA Collisions at Forward Rapidity - Ye-Yin Zhao; Ya-Hui Chen; Ya-Qin Gao; Fu-Hu Liu (Advances in High Energy Physics)
The inclusive particle productions in proton-proton (pp) and deuton-gold (d+Au) collisions at forward rapidity at the Relativistic Heavy Ion Collider (RHIC) energy are studied in the framework of the color glass condensate (CGC) theory by using two different initial conditions: AAMQS (Albacete-Armesto-Milhano-Quiroga-Salgado) and quartic action. Then, the results obtained by the two different initial conditions in illustrating the effect of valence color charges in high-energy proton-nucleus (pA) collisions at forward energy are compared. Meanwhile, the inclusive particle productions in pA collisions at forward rapidity at the Large Hadron Collider (LHC) energies are predicted. The main dynamical input in our calculations is the use of solutions of the running coupling Balitsky-Kovchegov equation tested in electron-proton (ep) collision data. Particle production is computed via the hybrid formalisms to obtain spectra and yields. These baseline predictions are useful for testing the current understanding of the dynamics of very strong color fields against the upcoming LHC data.